Optimal Integrated Diesel Grid-renewable Energy System for Hot Water Devices. (December 2016) - Wanjiru, Evan M.; Sichilalu, Sam M.; Xia, Xiaohua
Abstract: Many remote areas in developing countries such as Africa and island developing nations rely on expensive diesel grid even though there is a high potential for renewable sources such as wind and solar. Further, in domestic houses, water heating contributes to a huge percentage of the overall electricity consumption. Therefore, integration of renewable energy and efficient water heating systems would lower the electricity cost and greenhouse gas emissions. This paper introduces an optimal control model for a hybrid heat pump and instantaneous water heaters powered using integrated energy systems. The model can lead to 5.5% of power-not-delivered and 24% water savings.